Effect of Debt Level and Liquidity on Dividend the Pharmaceutical Sub-Sector Listed on the IDX from 2015 to 2020 - Mohamad Safii; Hendy Surahman (YPPP AL-AMSI, 2023)
This study aims to determine the effect of debt levels and liquidity on profit persistence (an empirical study of companies in the pharmaceutical sub-sector consumer goods industry listed on the IDX for the 2015-2020 period). This type of research is a quantitative approach research with descriptive analysis method. Samples were taken using purposive sampling technique. A sample of 60 data from 10 companies in the pharmaceutical sub-sector consumer goods industry listed on the Indonesia Stock Exchange in 2015-2020. The data analysis technique used is descriptive statistical techniques and panel data regression using Eviews 9. partially the debt level variable has no effect on dividends, partially the liquidity variable has no effect on dividends and simultaneously the level of debt and liquidity has a simultaneous effect on dividends.